Efficacy and safety of intermittent intravenous doxercalciferol in the treatment of secondary hyperparathyroidism in Chinese patients on maintenance hemodialysis: a phase II, open-label, prospective, multicenter study - Yang, Guang; Huang, Yaoyu; Ge, Yifei; Yu, Xiangbao; Liu, Li; Xiang, Li; Liu, Bin; Gao, Chaoqing; Liu, Changhua; Xu, Yong; Li, Wenwen; Lou, Donghua; et al. (Frontiers in Pharmacology, 2025)
ObjectiveThis phase II, open-label, prospective, multicenter study evaluated the efficacy and safety of intermittent intravenous doxercalciferol in treating secondary hyperparathyroidism (SHPT) in Chinese maintenance hemodialysis (MHD) patients.MethodsMHD patients aged 18 to 75 years with a serum intact parathyroid hormone (iPTH) level of 400 pg/mL or higher were enrolled and stratified into Mild, Moderate, and Severe groups based on baseline iPTH levels (400–599.99, 600–799.99, and ≥800 pg/mL, respectively). Patients received an initial dose of 4 μg of doxercalciferol three times weekly for 12 weeks, with subsequent dose adjustments to target iPTH levels of 150–300 pg/mL.ResultsOf the 45 patients enrolled, 44 completed the study, with 20 patients in the Mild Group, 12 in the Moderate Group, and 12 in the Severe Group. The baseline iPTH level for the 44 patients was 655.05 (469.68, 831.40) pg/mL, which decreased to 269.90 (176.45, 365.65) pg/mL after 12 weeks of treatment. The overall mean percentage change in iPTH levels from baseline to week 12 was −55.45% ± 20.08%, with 86.4% of patients (38 cases) achieving a ≥30% reduction compared to baseline. At week 12, 80.00% of patients (16 cases) in the Mild Group had iPTH levels within the target range of 150–300 pg/mL or less than 150 pg/mL, compared to 41.76% (5 cases) in the Moderate Group and 33.33% (4 cases) in the Severe Group. All three groups showed a decrease in serum alkaline phosphatase (ALP) levels, with the Severe Group experiencing a statistically significant reduction (P = 0.001). The most common adverse event was hypercalcemia, occurring in 33.3% of patients (15 cases), with only 8.9% (4 cases) experiencing severe hypercalcemia (serum calcium >2.8 mmol/L). Hypercalcemia was resolved after dose reduction or discontinuation of the medication.ConclusionIntermittent intravenous doxercalciferol effectively reduces iPTH levels in Chinese MHD patients, with a manageable safety profile. While hypercalcemia is a concern, the incidence of severe cases is not high. This study supports doxercalciferol as a potential treatment option for SHPT in Chinese MHD patients.Clinical Trial Registration:https://www.chictr.org.cn/showproj.html?proj=187332, identifier ChiCTR2300073196.